(untitled) (JOURNAL OF LANDSCAPE ECOLOGY | TÁJÖKÖLÓGIAI LAPOK, 2010)
The land, as a multifunctional resource, and its sustainable usage play key role in the improvement and development of rural areas. Sustainable land usage issues require the development of land use in each every case where the social-economical processes are in conformity with the natural systems on the long run. As a result of sustainable land usage and utilization, land can serve different functions conforming with the ecological, social and economical aspects. Human activities resulted in undesirable changes in the quality of land, fauna and flora and environmental elements that caused land usage conflicts and which influence the social-economical processes unfavourably on the short or long term. Therefore, regional conditions, the structure and function of the land and environmental capacities shall be taken into consideration in the land usage issues.The aim of our research is to analyze the land usage and land surface changes caused by social-economical processes since 1990 in the Hódmezővásárhely micro-region. In the paper we will present briefly how changes in land surface can be related to land use changes identified by using descriptive data. Based on the results, we will draw up land use suggestions for the micro-region taking the sustainability issues into consideration. Since the area has homogeneous agricultural characteristics, in the first place our suggestions will focus on the preservation and development of the remained farms, the propagation of ecological agriculture and, related to the artificial relieves (villages, cities, infrastructure, etc.), fitting the built up properties into the scenery with the minimal environmental impact possible which issues cannot be enforced without landscape designing and country planning.